As ações em saúde mental nos Núcleos de Apoio à Saúde da Família - NASF - Felix, Shenia Maria Felicio (2013)
The National Police for Basic Care (PNAB), regulated by ordinance nº2488 from October 2011, restates the Family Health Strategy (ESF) as a priority to the expansion, consolidation and qualification of basic attention to health matters in Brazil. In order to bring it about, city counsellors along with other federal entities ought to ordinate their work process deepening principals, directions and fundaments of Basic Care (AB). Besides ESF, the new PNAB expatiates on the Family Health Support Centres (NASF), reaffirming their role on broadening the scope of basic care actions and their improvements, ratifying their ability to share knowledge and support Basic Care professionals. All this considered, the purpose of this work is to investigate how NASF is currently structured in João Pessoa and what has been achieved by it on what concerns to mental health. Its main objectives are to analyse the practices of mental health professionals that are part of NASF teams and if they differ from what has been developed by the other members of the teams; to discuss the articulation of NASF in managing mental health measures on what concerns to internal organisatio n and to the city health network; to identify strategies used to organise such measures on mental health in Basic Care. To reach such goals, individual interviews have taken place two city health managers and four of NASF professionals that participated on the Mental Health Office as representatives of their sanitary districts. Also a focal group formed by various supporters of NASF was created, contemplating the diversity of professional categories involved with the teams and sanitary districts. It was possible to identify in NASF, in João Pessoa, an organisation based by the matrix support in which both management and basic care demands reflect a series of actions developed alongside with ESF. Amongst such actions, matrixing, home visits and the Singular Therapeutic Project (PTS) stand out. These activities have been discussed on the focal group and integrate the daily work of all NASF supporters despite their professional categories. NASF presents itself as a powerful strategy to SUS proper qualification and support to strengthen Basic Care and broaden family health teams‟actions.